Perfil epidemiológico de salud bucal (higiene oral, fluorosis, caries dental, enfermedad periodontal) y conocimientos, actitudes y prácticas en escolares de 6 -12 años del colegio Silveria Espinosa de Rendón 2020-1 (2020)
Introduction: Oral health is part of general health and well-being and contributes to the development of a healthy child. Oral health should be one of the priorities in the public health of the countries together with the control of risk factors. Among the most common oral diseases in children are dental caries, dental fluorosis, malocclusions, sometimes and a high plaque index, which can trigger gingival inflammation. Objective: To establish the state of oral health (oral hygiene, dental fluorosis,caries and periodontal disease) and the degree of knowledge in oral health of schoolchildren from 6 to 12 years of age at the Silveria Espinosa de Rendon school. Materials and methods: a descriptive observational cross-sectional study was carried out in 120 schoolchildren between 6 and 12 years of age at the Silveria Espinosa de Rendon School. Two types of instruments were applied to determine the degree of knowledge in oral health of schoolchildren. Likewise, the Silness & Löe, Russell, modified ICDAS, DEAN indices were applied. There was a standardization and previous calibration in the application of the indices. The prevalence of pathologies and the degree of severity were determined, according to sex, age, and level of education. Results: The state of oral hygiene in schoolchildren is deficient with 73%, the prevalence of caries is 94%, the experience of caries with modified POP was 4.6 / 22 and for caries with conventional COP it was 1, 40/22. For periodontal disease, the general average was 0,067. The DEAN index was found to be 1,06. The knowledge of schoolchildren from 2nd to 4th grade on oral hygiene and the elements to be used are regular, unlike in 5th graders their knowledge of the subject is good, attitudes for this 2nd to 4th group are regular and in the same way, for both groups the practices related to oral hygiene are regular. Conclusion: The high frequency of bacterial plaque on the surface demonstrated the poor oral hygiene status in the sample, as well as the prevalence of dental caries. Despite the oral hygiene condition, periodontal disease has not been established in schoolchildren. The community DEAN found in the sample can be considered a moderate risk to public health. The continuity of the promotion and prevention activities at the Silveria Espinosa de Rendón School is necessary.